The Normative Enactment of International Cybersecurity Capacity Building Assistance: A Comparative Analysis on Japanese and South Korean Practices - Bimantara, Azza (Global: Jurnal Politik Internasional, 2022)
The international community encourages states to embrace the international cooperation to support and assist each other in reducing risks stemming from the digital divide. However, they cannot agree upon how international norms apply to cyberspace, let alone shaping and regulating international cybersecurity capacity building (CCB) assistance. States use international CCB assistance to impose cyber-norms based on their perceptions. It results in different forms of assistance provided by each donor country. Using social constructivism theory and the CCB concept as international assistance, this paper compares the practice of CCB assistance from two donor countries: Japan and South Korea. It emphasises the role of each donor country’s normative structure in shaping their identities, roles, interests, and behaviours in international CCB assistance. Japan’s international cybersecurity cooperation normative structure shapes Japan’s identities and roles that prioritise security-dominant normative and material interests. Meanwhile, South Korea’s developmental focus constructs the country’s identities and roles that shape developmental normative and material interests. This research finds that Japan’s assistance is highly security-oriented while South Korea’s is less security-oriented. Their differences highlight the fragmentation of global cyber-norms caused by different perception processes.